2009
DOI: 10.1109/tap.2009.2027040
|View full text |Cite
|
Sign up to set email alerts
|

Compact Patch Antenna for Electromagnetic Interaction With Human Tissue at 434 MHz

Abstract: Single element loop, dipole and conventional square patch antennas have been used as hyperthermia applicators in the treatment of cancerous human cells at superficial depths inside the body. A smaller novel patch antenna in very close proximity to a phantom tissue model produces an enhanced specific absorption rate pattern without significant frequency detuning or impedance mismatch. The new patch increases its coupling aperture by supporting a combination of resonances that are also typical for loop, dipole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Large matched impedance bandwidth is therefore desirable to enhance the overall system stability. The applicator should present tangentially aligned E-fields to improve energy deposition into the breast tissue, avoid hot spots in the skin, and to reduce the power required to couple energy into the tumour volume [31,37]. Avoiding the use of impedance matching circuits increases system eHciency and simplifies clinical integration.…”
Section: Design Objectivesmentioning
confidence: 99%
“…Large matched impedance bandwidth is therefore desirable to enhance the overall system stability. The applicator should present tangentially aligned E-fields to improve energy deposition into the breast tissue, avoid hot spots in the skin, and to reduce the power required to couple energy into the tumour volume [31,37]. Avoiding the use of impedance matching circuits increases system eHciency and simplifies clinical integration.…”
Section: Design Objectivesmentioning
confidence: 99%
“…Experts suggested that to detect it as early as possible and to treat it. For treatment of tumourswhich are located close to the surface of the body, theelectromagnetic field energy is applied through externalantennas (applicators) [1], [2], [3]. Instead of treating any disease, prevention is far better option.…”
Section: Introductionmentioning
confidence: 99%
“…As described before and in case of a single channel measurement, the dielectric properties of the medium change (shift) the central frequency (the frequency in which we have matching the input impedance) of the channel, so if we have a common antenna system the measurement would not be accurate, and we use the reconfigurable concept of a previous work of the authors [13] in which a set of varactor diodes are used to change the resonant frequency on demand [14][15][16].…”
Section: Introductionmentioning
confidence: 99%